Effect of TIMP2/TIMP3 genes on the risk of osteosarcoma in Zhejiang population. Issue 11 (19th March 2021) - Wu, Zhongwei; Chen, Huali; Pan, Liwei; Yu, Weiyang; Lou, Chao; Chen, Jian; He, Dengwei
Abstract : Abstract: Osteosarcoma is a malignant tumor that develops from a mesenchymal cell line and is caused by gene–environment interactions. This study aimed to explore whether TIMP2 / TIMP3 polymorphisms influenced the osteosarcoma risk. The expression of the TIMP2 and TIMP3 genes in osteosarcoma histiocytes was analyzed by immunohistochemistry. In this case-control study, which includes samples from 499 patients and 500 healthy controls, 10 single-nucleotide polymorphisms (SNPs) in TIMP2 and TIMP3 were selected. Furthermore, we used the Agena MassARRAY platform for genotyping. The statistical analysis was performed using χ 2 test/Fisher exact test, and logistic regression analysis. The immunohistochemistry results showed that the expression of TIMP2 is obvious higher in osteosarcoma histiocytes than in the normal histiocytes. The association study indicated that the allele of rs2277698 and rs4789936 were protective SNPs reducing the risk of osteosarcoma (odds ratios  > 1, P  < .05) by the χ 2 test. In the genetic model, logistic regression analyses revealed that the rs2277698 and rs4789936 were associated with decreasing the risk of osteosarcoma under the codominant model, dominant model, and log-additive model. Stratification analysis revealed that 2 SNPs (rs2277698 and rs4789936) were significantly associated with a reduced risk of osteosarcoma in allele and genetic model after stratification by gender or age ( P  < .05). In addition, the haplotype "Trs2277698 Crs2009169 Crs7342880 " of TIMP2 was associated with decreasing the osteosarcoma risk. The "Ars9609634 Trs11547635 " of TIMP3 was associated with reducing the osteosarcoma risk. This finding shed new light on the high expression of TIMP2 polymorphisms may contribute to decreasing the osteosarcoma risk in Zhejiang populations.